2013
DOI: 10.1177/1357633x13476231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an off-the-shelf mobile telemedicine model in emergency department wound assessment and management

Abstract: We examined the agreement between a videoconference-based evaluation and a bedside evaluation in the management of acute traumatic wounds in an emergency department. Adult and paediatric patients with acute wounds of various severities to the face, trunk and/or extremities presenting to the emergency department within 24 hours of injury were enrolled. Research assistants transmitted video images of the wound to an emergency physician using a laptop computer. The physician completed a standard wound assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…19 Only a single app was used in each study; none compared performance of several apps on different wireless networks. Moreover, transmission rates were unspecified in many studies, 11,[16][17][18] another image quality factor. 19 References to Universal Mobile Telecommunications Systems without specifying the technology's iteration (e.g., 3G or 4G) were often made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Only a single app was used in each study; none compared performance of several apps on different wireless networks. Moreover, transmission rates were unspecified in many studies, 11,[16][17][18] another image quality factor. 19 References to Universal Mobile Telecommunications Systems without specifying the technology's iteration (e.g., 3G or 4G) were often made.…”
Section: Introductionmentioning
confidence: 99%
“…7 Eleven studies had more than one teleconsultation involving physicians or other health providers. [8][9][10][11][12][13][14][15][16][17][18] They included, for example, studies of 3G cellular networks with transmissions of 64 kilobits/s (Kbps) for cardiopulmonary resuscitation assistance with and without video, 8 video with multiplexed 3G networks (combining multiple 3G data streams into a single signal) to achieve transmissions of 125-150 Kbps from moving ambulances to transmit endotracheal intubations and ultrasound, 9 and video telestroke consultations with land line transmissions over 700 Kbps and 3G wireless transmissions as low as 128 Kbps. 10 Overall, the studies suggest that there may be lower boundary transmission rates below which the data transmitted become unusable.…”
Section: Introductionmentioning
confidence: 99%
“…Van Dillen, et al [47] Outcome: Comparing accuracy of wound image 39 Chen, et al [48] Outcome: Comparing accuracy of assessment 40 Dobke, et al [15] Outcome: Satisfaction and decisional conflict scale score 41 Houghton, et al [49] Outcome: Comparing accuracy of assessment 42 Bowling, et al [50] Outcome: Comparing accuracy of assessment 43 Gardner, et al [51] Outcome: Comparing accuracy of assessment 44 Debray, et al [52] Outcome: Comparing accuracy of assessment 45…”
Section: Study Selectionmentioning
confidence: 99%
“…Hofmann-Wellenhof, et al [53] Outcome: Comparing accuracy of assessment 46 Ratliff, et al [54] Outcome: Evaluate cost saving and quality of care 47 Halstead, et al [55] Outcomes: Comparing accuracy between tele and in-person assessment 48 Saffle, et al [56] Outcome: Improve resource utilization 49 Clegg, et al [57] Outcome: Cost saving 50 Rasmussen, et al [58] Outcome: Comparing accuracy between tele and in-person assessment 51 Braun, et al [59] Outcome: Feasibility 52…”
Section: Study Selectionmentioning
confidence: 99%
“…4 Reliable interpretation of physical signs in pediatric patients is important for illness management and transfer decision. Several studies in children comparing TM with traditional face-to-face (FTF) evaluation of patients have shown that TM is an effective tool in clinical evaluation of acute minor illnesses, 5 wound and minor injury assessment, [6][7][8] and burn assessment. 9 These studies have used simple video consultation for children with noncritical illnesses.…”
mentioning
confidence: 99%